Fbw7 Inhibits the Progression of Activated B-Cell Like Diffuse Large B-Cell Lymphoma by Targeting the Positive Feedback Loop of the LDHA/lactate/miR-223 Axis - Yao, Su; Guo, Tairan; Zhang, Fen; Chen, Yu; Xu, Fangping; Luo, Donglan; Luo, Xinlan; Lin, Danyi; Chen, Wendan; Li, Zhi; Liu, Yanhui (Frontiers in Oncology, 2022)
Background F-box and WD repeat domain-containing 7 (Fbw7) is well known as a tumor suppressor and ubiquitin ligase which targets a variety of oncogenic proteins for proteolysis. We previously reported that Fbw7 promotes apoptosis in diffuse large B-cell lymphoma (DLBCL) through Fbw7-mediated ubiquitination of Stat3. This study aimed to identify the mechanism of Fbw7-mediated aerobic glycolysis reprogramming in DLBCL. Methods Expression levels of Fbw7 and Lactate Dehydrogenase A (LDHA) in human DLBCL samples were evaluated by immunohistochemistry. Crosstalk between Fbw7 and LDHA signaling was analyzed by co-immunoprecipitation, ubiquitination assay, western blotting and mRNA quanlitative analyses. In vitro and in vivo experiments were used to assess the effect of the Fbw7-mediated LDHA/lactate/miR-223 axis on DLBCL cells growth. Results Fbw7 could interact with LDHA to trigger its ubiquitination and degradation. Inversely, lactate negatively regulated Fbw7 via trigging the expression of miR-223, which targeted Fbw7 3’-UTR to inhibit its expression. In vivo and in vitro experiments revealed that miR-223 promoted tumor growth and that the effects of miR-223 on tumor growth were primarily related to the inhibition of Fbw7-mediated LDHA’s ubiquitination. Conclusions We demonstrated that the ubiquitin-ligase Fbw7 played a key role in LDHA-related aerobic glycolysis reprogramming in DLBCL. Our study uncovers a negative functional loop consisting of a Fbw7-mediated LDHA/lactate/miR-223 axis, which may support the future ABC-DLBCL therapy by targeting LDHA-related inhibition.